Study on the Influence of Piloti Ratio on Residential Block’s Wind Environment by Coupled Simulation Method - Xi Tianyu; Ding Jianhua; Jini Hong (MATEC Web of Conferences, 2017)
The environmental degradation results in not only the increase of energy consumption in cities but also healthy problem of people, and many researches regarding to outdoor environment and thermal comfort are carried out. Wind velocity is considered to be one of the thermal comfort influential factors, and there are few work studied the comprehensive influence of piloti on wind environment by coupled simulation method, which offers high precision CFD simulation results. This paper taking the city of Guangzhou, China, as an example, adopting coupled simulation method, studied the wind environment of residential blocks under various piloti ratio (0%, 40%, 60%, 80 and 100%). Both of the cumulative distribution and average wind velocity under piloti and out of piloti area are simulated and analysed. This work is expected to offer reference for architects and civil engineers in outdoor environment and thermal comfort design, and contribute to further study in sustainable and healthy building environment research field.